Pancreatic duct cell carcinoma with positive 111In octreotide uptake - (:unkn) unknown (My University, 2000)
Duct cell adenocarcinomas may produce neuroendocrine markers such as pancreatic polypeptide, gastrin and gastrin releasing hormones. A 53 year old patient, with a history of insulin dependent diabetes, was found to have a pancreatic mass which was later pathologically demonstrated to be a duct cell adenocarcinoma. The tumor produced elevated circulating neuroendocrine markers specifically gastrin and pancreatic polypeptides. An rain Octreotide imaging showed definite uptake of Octreotide by the tumor. The patient was subsequently treated with Somatostatin analog which resulted in the reduction of some of the circulating endocrine markers. The patient had essentially six months of asymptomatic clinical remission but then she relapsed. Octreotide scanning could be useful for selected patients with pathologic diagnosis of duct cell adenocarcinoma, because some tumors may have neuroendocrine features and can be imaged, and might even respond to Somatostatin analog therapy.
Keywords: 111Indium; Octreotide; Pancreatic carcinoma; Scintigraphy; Somatostatin